Payment issues in telecommunication infrastructure project - Sheikh Mohd Shahrien Sheikh Razman, 1979-, author 610797; Maizon Hashim, supervisor 577586; Fakulti Alam Bina 8041 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan))